DEFINING AND FIGHTING ORGANISED CRIME IN POLISH SUBSTANTIAL CRIMINAL LAW - Michalska-Warias Аneta (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Polish criminal law does not use the term “organised crime” and, since criminological definitions of that term are to serve different purposes, they are of limited usefulness for defining the terms which refer to organised criminal activity in the legal statutes. Article 258 of the binding Criminal Code of 1997 clearly states that whoever the participates in an organised group or association which have the aim to commit an offence or a fiscal offence is guilty of a misdemeanor punished with imprisonment from 3 months to 5 years. If the group or association is armed with weapons or intends to commit a terrorist-type offence, the punishment is from 6 months to 8 years of imprisonment, and the punishment becomes even higher if the offender is guilty of establishing or directing such criminal structures. The definition of these two types of criminal bodies is left to the courts and scholars and there is a general consensus that both types of structures have to consist of at least three members, both have to present some stability in time (so they cannot be randomly formed for the immediate commission of the offence) and in order to be organised both need to manifest some kind of structure, while the main difference between them lies in the achieved organisational level which is higher in the case of a criminal association. Yet, it has to be stressed that distinguishing the two forms can only be done in concrete cases since both an association and a group can have only 3 members and then the requirements connected with considering such entities organised would be different than in the cases of more numerous structures. On this basic level it can be argued that a criminal association absolutely needs to have a leader (and a hierarchy), while this is not necessary in the case of smaller organised criminal groups. This interpretation can be also be inferred from some Supreme Court judgments referring to the practical application of Article 258 of the Criminal Code. The substantial criminal law framework of responsibility for crimes committed by organised structures is complemented by some general part solutions which create both the obligation to aggravate the punishment for offenders belonging to criminal groups (Article 65 of the Criminal Code) and create the possibility to reduce the responsibility of those gang members who decide to co-operate with the law enforcement organs and reveal the circumstances of the offence and the identity of the other perpetrators (Article 60 § 3-5 of the Criminal Code).